THE INFLUENCE OF INFLATION, EXCHANGE RATE, AND BI RATE ON THE INDONESIAN SHARIA STOCK INDEX (ISSI) - Alfin Maulana; Yoan Maris (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
This research aims to test and analyze the influence of inflation, exchange rate and BI rate on the Indonesian Sharia Stock Index (ISSI). This type of research is an associative quantitative approach. Data analysis was carried out using statistics with the SmartPLS 3.0 tool. The results of data analysis using the Estimate for Path Coefficients significance test showed that partially inflation had a significant and positive effect on ISSI, the exchange rate had no significant and negative effect on ISSI and the BI Rate had no significant and negative effect on ISSI. Meanwhile, based on the results of the R Square test, simultaneously inflation, the exchange rate and the BI Rate have a significant and positive effect on (ISSI).